Time-Out for Young Children. Issue 1 (January 2017) - Beal, Judy A.
Abstract : Time-out is an evidence-based form of discipline that can be used by parents of young children. Pediatric nurses can assist parents to appreciate how to use time-out while supporting their decisions to implement or not.